Analisis Yuridis Pembuatan E-Ktp Di Batubara - Raja Aruan; Herlina Hanum Harahap (IHSA Institute, 2025)
This study aims to analyze the role of public services in the Indrapura District government of Coal Regency. Public services are all activities carried out by an organization or agency as an effort to fulfill the needs of the community. These services are carried out in accordance with laws and regulations with basic rules and procedures that have been determined by each organization or agency. Government apparatus and all its ranks are commonly known as state servants and public servants and simply put, this role is expected to be realized in providing various types of services to the community. The problem currently faced by Indonesia regarding the E-KTP case is the recent case of misuse of E-KTP funds. This is a major concern for all Indonesian people, and state officials. This problem has a very broad impact and results in losses to the state. This study recommends increasing supervision of e-KTP issuance services in the Indrapura District